The payroll & secretarial procedure of GlaxoSmithKline Bangladesh Limited and the employee satisfaction on it - Kabir, Farhan Fardeen (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.